Determinate Location Of MBKM Internship Based On Clusterring Student's Skills With K-Means (Case In Universitas PGRI Argopuro Jember) - Frida Murtinasari; Eric Dwi Putra (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
The purpose of this study was to determinate location of MBKM internship based on clusterring student's skills with K-Means. This is important to detect some of student’s skills which will become the output of the university that must be recorded early so that they were truly ready to compete. To analyze the skills of some students, the Mathematics Education study program at the University of Argopuro Jember conducted a survey of additional skills outside of lectures. This survey is carried out regularly every year as material for reporting on the development of students' skills and qualities. Thus the skills possessed by students can be monitored and evaluated whether in the future special skills were needed that must be given to students. The skills of students who become points in the survey include: 1)Foreign language skills, 2)IT Skills, 3)Public Speaking and Management Skills, 4)Analitical and Graphic Design Skills, 5)Microteaching Skills. We clustering 67 respondent, it is our student at Universitas Argopuro Jember in fiveth. Cause of outlier in 7 respondent, we just make clustering with K-means with 60 respondent. Based on K-Means clusterring we have 3 cluster .It shows that cluster 1 has 32 respondents, cluster 2 has 21 respondents and cluster 3 has 7 respondents. Abd also on the result and discussion, we knew that cluster 1 with 32 respondent has more skills, it were foreign language, public speaking skills and microteaching skills. So the internship locations that match these skills clusters such as LBB then Publication Offices such as Radio, Jawapos, etc. For second conclusion, we knew that cluster 2 with 21 respondent have more skills except for microteaching skills. Appropriate internship places for these students are in administrative offices, local government offices, etc.And for third conclusion, that cluster 3 with 7 respondent have more skills too except public speaking but they have a middle skills in microteaching. The office or internship location where we can suggest is Dinas Parawisata, Perbankan that needs good communication and good team work, etc